Edible marine algae: a new source for anti-mycobacterial agents - Mukherjee, Goutam; Mukhopadhyay, Balaram; Sil, Alok Kumar (Folia microbiologica, 2021)
Tuberculosis is a dreaded disease, which causes innumerable death worldwide. The emergence of drug resistance strains makes the situation devastating. Therefore, for better management of public health, it is mandatory to search for new anti-mycobacterial agents. In this context, the current study investigated two edible marine algae, Ulva lactuca and Ulva intestinalis, for the probable source of new anti-mycobacterial agents. To test the anti-mycobacterial activity, alcoholic extracts of these two algae were spotted on the Mycobacterium smegmatis lawn. Upon incubation, clear zone was observed at the spots. It indicated that these two extracts have anti-mycobacterial activity. In addition, their anti-biofilm property was also tested. It was found that both the extracts inhibit the mycobacterial biofilm development as well as they can disperse the preformed mycobacterial biofilm. Since these two are capable of dispersing preformed mycobacterial biofilm, it is possible that in the presence of either of these two extracts, isoniazid and rifampicin can kill biofilm encapsulated mycobacterium in combinatorial therapy. Consistent with the hypothesis, rifampicin and isoniazid killed mycobacteria that were present in biofilm. Thus, these two extracts augment the activity of rifampicin and isoniazid upon biofilm dispersal. Moreover, treatment of different cell lines with these two extracts exhibited no or little cytotoxic effects. Thus, these two agents have the potential to be good therapeutic agents against mycobacterial diseases.
Keywords: Rifampin; Animals; Ulva; buněčné linie; mikrobiální testy citlivosti; rostlinné extrakty; rifampin; lidé; Anti-Bacterial Agents; Cell Line; Microbial Sensitivity Tests; mořské řasy; Mycobacterium smegmatis; isoniazid; Drug Synergism; Isoniazid; Plant Extracts; synergismus léků; Cell Survival; biofilmy; zvířata; viabilita buněk; antibakteriální látky; Biofilms; Seaweed; Humans